The Influence of the Mixed Electric Line Poles on the Distribution of Magnetic Field - Ghanim Thiab Hasan; Ali Hlal Mutlaq; Kamil Jadu Ali (IAES Indonesian Section, 2022)
With the wide spread of the transmission line